EXPLORING THE IMPACT OF GENDER EQUALITY ON LANGUAGE LEARNING OUTCOMES: A COMPARATIVE ANALYSIS OF EDUCATIONAL PRACTICES AND STUDENT EXPERIENCES - Sobirova Elgiza Alibek kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
The connections between language acquisition and gender equality has been a crucial topic of inquiry in educational studies in recent years. The impact of gender dynamics  on  language  learning  and  its  consequences  for  instructional  strategies  in various educational situations are examined in this study. The study draws attention to enduring  differences  in  language  learning  outcomes  across  genders  by  examining historical and modern viewpoints on gender in education. It examines the theoretical frameworks  that  support  these  processes,  such  as  feminist  pedagogy  and  social constructivism, and it surveys the body of research that shows the nuanced connection between language competency and gender norms. This study uses a mixed-methods approach in terms of methodology, combining qualitative information from interviews and classroom observations with quantitative data from language competency tests. Students  from  a  variety  of  backgrounds  participate,  enabling  a  comprehensive knowledge of the experiences of various genders in language learning settings. The results  show  that  boys  usually  show  more  confidence,  although  girls  tend  to  show stronger language ability and involvement, indicating that socialization and cultural expectations greatly influence their experiences.